Face-Threatening Acts and Face-Invading Acts of Students’ Asynchronous Conversation in Online Learning - Imam Santosa; Ifan Iskandar (English Education Department, 2022)
This research aimed to examine the use of FTA and FIA in communication of online learning during covid 19 outbreak. Descriptive qualitative study was exploited to answer the research question. The communication between teacher and student in WhatsApp group during online learning was main focus of this study. The group consisted of 15 courses taught by 7 lectures. The result of the study showed that the most frequent utterance used was directive which outnumbered all categories with 38%. Declarations 36%. Commissive, expressive and assertive got the smallest proportion with 12%, 8% and 6%. Moreover, there was not the existence of FIA found in the lecturer’s utterance. Meanwhile, the utterance of FTA by lecturer showed that 70 % as hearer negative face that bind student freedom. Speaker negative face followed in the second highest number with 23 percent. Both positive face either speaker and hearer got 7% of all utterances. The hearer negative face in directive utterance turned out to be the most appearance by the lecturer on 34.11%. This followed closely by the negative face in declaration by 21.57%. The unique thing existed on how commissive act in both speaker and hearer negative face got 10.50% and 11.08 %. This concluded that the authority of the teacher led the use of hearer negative FTA that constraints student freedom. However, the students were also aware the status as learner, hence student did not feel threatened.